Indicators of students’ readiness for physical exercise - Glazkova, G.B.; Mamonova, O.V.; Dubrov, A.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify effective aspects of physical education for university students, taking into account their level of readiness for physical activity. Methods and structure of the study. Research was conducted at Plekhanov Russian University of Economics, comprising: a review of the literature; a survey of first-year students (healthy students (n=390) and students with health issues (n=390)); and predictive modelling of students’ physical education. Results and conclusions. The experiment involved students from health groups I and II (the general medical group, GMG) and health group III (the special medical group, SMG). Priority forms of physical activity at school (team sports, gymnastics, athletics and ski training), as first-level predictors, were taken into account in the predictive modelling of students’ physical education (PE): the introduction of priority types of sports games at school and physical education (PE) lessons, as well as sports clubs, including those for SMG students (taking into account their state of health). Factors increasing and decreasing students’ physical activity as second-level predictors determine the prognostic significance for the modernisation of PE: professional development of specialists in priority types of sports games at school and corresponding types of phygital sports; the application of digital technologies in the physical education and sports process, including with SMG students; the introduction of soft and neuroscientific sports activities into lessons. The identified predictors of students’ readiness for physical activity formed the basis for predictive modelling of PE, extrapolating positive experiences of participation in clubs for priority sports to achieve a cumulative effect in improving young people’s health.